A Cross-Sectional Study of the Prevalence of Short Stature Among Children Visiting the Outpatient Department of a Tertiary Care Center - Shrivastava, Dr. Mohit; Anand, Dr. Shweta (Indian Journal of Child Health, 2024)
Background: Short stature in children is a significant global health concern, often indicating underlying nutritional, endocrine, or genetic disorders. Identifying the prevalence and associated risk factors in specific populations in regions with limited access to healthcare, poor nutrition, or inadequate prenatal care eg in rural or low-income communities, is essential for early diagnosis and timely intervention. Objective: This study aimed to assess the prevalence of short stature among children visiting the outpatient department of a tertiary care center and to explore the sociodemographic (lower SES, nuclear families) and clinical factors {chronic illness like hypothyroidism, diabetes, and bone age} associated with short stature. Methods: A cross-sectional observational study was conducted at the Department of Pediatrics, LN Medical College, and JK Hospital, Bhopal. A total of 210 children aged 2-12 years attending the outpatient department were systematically selected (systematic sampling) and approved by the IEC. Inclusion criteria involved children whose parents or guardians provided informed consent, while exclusion criteria included children with hypotension or those whose guardians did not consent. Anthropometric measurements, clinical assessments, and family histories were recorded. Short stature was defined as height-for-age below -2 standard deviations from the WHO growth standards. Results: The prevalence of short stature was 4.29%. It was more common among children from lower socioeconomic backgrounds (55.6%) and nuclear families (66.7%). The highest prevalence was observed in children aged 5-8 years (77.8%), with no significant gender difference. Additionally, 77.8% of children with short stature had a chronic illness, such as hypothyroidism or diabetes. And 88.9% showed delayed bone age. The influence of maternal education was also significant, with 55.6% of affected children having illiterate mothers. Conclusion: The study found a relatively lower prevalence of short stature compared to other studies, but it was significantly associated with lower socioeconomic status, chronic illness, delayed bone age, and maternal education. Early detection, nutritional interventions, and addressing socioeconomic disparities, enhancing maternal education are essential to improve growth outcomes in children. Further research is needed to investigate the long-term outcomes of children with short stature and the effectiveness of targeted interventions.